The Development of Mathematics Comic Containing Pancasila Values to Develop Character of Elementary School Students: A Case Study of Indonesia - Farid Ahmadi; Rochmad Rochmad; Farida Puput Lestari; Dewanto Harjunowibowo (Journal of Innovation in Educational and Cultural Research, 2021)
The present research focuses on developing mathematics comic as a teaching material that integrates the moral value of discipline and hard work for elementary school students. This character-building comic development method was made based on the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Twenty-nine grade four students were recruited as samples, consisting of a small group of students in the limited trial group and a big group of students in the field trial group. The data collection technique used was a questionnaire. The development of mathematics comic teaching material containing discipline and hard work character-building has successfully resulted in a comic that met the feasibility standards. The field trial showed a significant increase of 0.76 and 0.74 in students’ character development in terms of discipline and hard work, respectively. The results indicate the effectiveness of mathematics comics in instilling Pancasila moral values in elementary mathematics teaching in Indonesia.